Sistem Pendukung Keputusan Pemilihan Calon Barista Dengan Menggunakan Metode DEMATEL Dan WASPAS (Studi Kasus : Coffee Corner Medan) - Yatatema Kristian Gulo (STMIK Budi Darma, 2021)
Currently, at the Coffee Corner Medan, of course there are many prospective baristas who have different backgrounds, for example, someone who already knows the types of coffee and how to make it, of course the prospective barista is worthy of being a potential barista. In the process of selecting prospective baristas at the coffee corner of Medan, they are still selecting intuitively or feeling and the judging system is still not computerized. Therefore, to make it easier to choose, you can use the computerized Dematel and Waspas methods to get better results. The Dematel method is used to determine the relationship between the performance evaluation criteria used. The dematel method is one of the best methods that can be used to determine and analyze the dominant characteristics of a system. The waspa method is to find the priority of selecting the location that best fits the weighting. In the application of the two-element combination waspas method known as MCDM Mapproaches, WMM and heavy product model (WPM) and initially requires linear normalization of the yield elements. Although it does not guarantee its efficiency, using this method can help decision makers in making decisions more accurately in selecting candidates for barsta in the coffee corner of Medan